Adrenalectomy for Metastatic Melanoma: Current Role in the Age of Nonsurgical Treatments. Issue 10 (October 2015) - Flaherty, Devin C.; Deutsch, Gary B.; Kirchoff, Daniel D.; Lee, Jihey; Huynh, Kelly T.; Lee, David Y.; Foshag, Leland J.; Bilchik, Anton J.; Faries, Mark B.
Surgical resection of metastases to the adrenal gland can improve overall survival of patients with stage IV melanoma, but its relative value with respect to current nonsurgical therapies is unknown. We hypothesized that surgery remains an optimal first-line treatment approach for resectable adrenal metastases. A search of our institution's prospectively collected melanoma database identified stage IV patients treated for adrenal metastases between January 1, 2000, and August 11, 2014. The 91 study patients had a mean age of 60.3 years at diagnosis of adrenal metastasis and 24 had undergone adrenalectomy. Improved survival was associated with an unknown primary lesion, surgical resection, and nonsurgical therapies. Median overall survival from diagnosis of adrenal metastases was 29.2 months with adrenalectomy versus 9.4 months with nonoperative treatment. Adrenalectomy, either as complete metastasectomy or targeted to lesions resistant to systemic therapy, is associated with improved long-term survival in metastatic melanoma.